Integration of sexually transmitted infection and HIV pre-exposure prophylaxis services in sub-Saharan Africa: a scoping review - Anand, Priyanka; Wu, Linxuan; Mugwanya, Kenneth (Frontiers in Reproductive Health, 2023)
Background: Persons living in Sub- Saharan Africa (SSA), face disproportionate risk from overlapping epidemics of HIV and bacterial sexually transmitted infections (STIs). Pre-exposure prophylaxis (PrEP) for prevention is gradually being scaled up globally including in several settings in SSA, which represents a key opportunity to integrate STI services with HIV pre-exposure prophylaxis (PrEP). However, there is limited literature on how to successfully integrate these services in SSA.Prior studies and reviews on STI and PrEP services have largely focused on high income countries. Methods: We conducted a scoping review of models of integration of STI and PrEP services in SSAWe searched PubMed, EMBASE, Cochrane, and CINAHL, in addtion to grey literation to identify studies that were published between January 2012 and January 2022, and provided STI and PrEP services with/without outcomes reported in SSA. Articles and abstracts were reviewed by two reviewers for inclusion. Full text were then retrieved and reviewed in full by two reviewers. Results: Our search strategy yielded 1751 records, of which 197 were retrieved in full and 44 reports of 33 studies included in our final review. Most studies were conducted in Southern (45.5%) and Eastern (29.5%) Africa. Service settings included public health clinics (34.1%), sexual and reproductive care settings (22.7%), maternal and child health settings (6.8%), community based services (11.4%), and mobile clinics (4.5%). About one-quarter (8/34) of the studies described only syndromic STI management while three-quarters (27/34) included some form of etiological laboratory STI diagnosis. STI testing frequency ranged from baseline testing only to monthly screening. Types of STI tested for was also variable. Few studies reported outcomes related to implementation of STI services. There were high rates of curable STIs detected by laboratory testing (baseline genitourinary STI rates ranged from 5.6-27.0% for CT, 0.0-11.2% for GC, and 0.4-8.0% for TV). Discussion: In this scoping review of STI and PrEP service integrations in SSA, we found that STI services were mostly provided as part of research studies with varied testing methods and types of STI tested along with PrEP provision, but limited evidence on from real world implementation studies.